Linked data for libraries, archives and museums : how to clean, link and publish your metadata - Hooland, Seth van; Verborgh, Ruben (Facet Publishing, 2015)
Seth van Hooland is associate professor at the Information and Communication Science department of the Universite libre de Bruxelles, where he holds the chair in Digital Information. Van Hooland is also active as a consultant for clients such as the European Commission and occasionally works for leading companies in the SemanticWeb industry such as Mondeca and Poolparty. Ruben Verborgh is a PhDresearcher in semantic hypermedia at Multimedia Lab - GhentUniversity - iMinds, Belgium. As a Master in Computer Science Engineering, he closely follows and participates in the latest evolutions on the W.